João do Vale e a invenção do nordeste: uma construção identitária regional na perspectiva de canções do ‘poeta do povo’ - Francisco Adelino de Sousa Frazão (2023)
This research was designed with the aim of understanding the strategies and elements (poetic, musical, interpretative) employed by João do Vale in the process of constructing a set of ideas about the “Nordeste brasileiro” through the analysis of the versions of the songs Minha história, Pisa na fulô, A voz do povo and Ouricuri (Segredos do sertanejo), present in the album “O poeta do povo” (1965). Additionally, the research sought to reflect on how this set of ideas interacts with the hegemonic representations built around the region. I start from the assumption that the organization of spaces, as well as their imagery-discursive and geographic creation, depends on the action of certain agents of a society, not being the result of chance or the action of nature. Among the personalities who contributed to the “invenção do Nordeste”, such as Euclides da Cunha, Gilberto Freyre, Djacyr Menezes, and Luiz Gonzaga, we also find João do Vale: a songwriter from Maranhão who developed a peculiar way of composing songs, capable of establishing connections between the genres of so-called “música nordestina”, MPB, samba, bossa nova, and politically engaged songs - something unprecedented in the Brazilian musical and phonographic scene of his time. In summary, this work aimed to reflect on João do Vale's trajectory, develop an analysis of the album “O poeta do povo” (1965), discuss the idea of the “invenção do Nordeste”, analyze four songs by João do Vale to understand how the songwriter constructs his vision of the “Nordeste”, and finally, compare the composer's perspective with the dominant ideology created about the region. By examining sound, lyrics, and performance in an integrated manner, it is evident that the meanings of the songwriter's works, even in songs aimed at different styles than the considered “música nordestina”, exhibit marks of an oral and peculiar sonority. The adopted methodology for analysis was based on an interdisciplinary approach in which the song is examined as a dynamic event, taking into account the organic integrity of the lyrics, sound aspects, and interpretive works within a specific historical, social, and cultural context. After the analysis, it was observed that João do Vale's songs were not based on any stereotypical, calamitous, negative, nostalgic, or rebellious representation of the “Nordeste”. Through his works, the composer elaborates a plural and multifaceted perspective of the region, creating and/or giving space and voice to a variety of possible “nordestinos” types.